Pengaruh Keselamatan Pekerja Terhadap Produktivitas Karyawan Pada Ben’s Cafe Medan. - Leonardo Indra Vitaharsa; Muhammad Halfi Indra Syahputra; Abdi Sugiarto; Khamo Waruwu; Yudi Syahputra (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The research was motivated by phenomena that were felt to be lacking in terms of worker safety in a job, then this paper aims to determine the effect of worker safety with indicators of work conditions and use of work tools on employee productivity at Ben's Cafe Medan. The research in this paper was carried out by Ben's Cafe Medan, with the subject of 30 employees taken as a whole from the research sample. The data used in this research is primary data. Test the data with the normality test, test for the presence or absence of homogeneity. using simple regression analysis with a significant limit of=0.05. The output of the results studied found: there is a significant effect of the worker safety variable on employee productivity with tcount 2.204 > ttable 2.042 and a significance level of 0.036 <0.05, which means that H0 is rejected and Ha is accepted. The SPSS output is obtained at an R square value of 0.384 with the assumption that worker safety has an influence on employee productivity of 38.4% and the remaining 61% is influenced by other indicators not included in this paper.